At home and in the field : ethnographic encounters in Asia and the Pacific islands. - Pigliasco, Guido Carlo; Pigliasco, Guido Carlo; Finney, Suzanne S.; Finney, Suzanne S.; Mostafanezhad, Mary; Young, Forrest Wade; Mostafanezhad, Mary (Honolulu : University of Hawaiʻi Press, 2015)
Crossing disciplinary boundaries, 'At Home and in the Field' is an anthology of twenty-first century ethnographic research and writing about the global worlds of home and disjuncture in Asia and the Pacific Islands. These stories reveal novel insights into the serendipitous nature of fieldwork.
Tempting the Naga: local knowledge and mysteries of the Mekong / Carl J. Hefner -- An anthropologist behaving badly: the case of the missing watch on Waya Island, Fiji / Lisa Humphrey -- Attacked in the field: encountering a street gang while studying peace in Java / Jaida Kim Samudra -- A question of permission in Pohnpei / Suzanne S. Finney -- Grandmothers, sharks and other dangerous things: persistent crises in Mangareva, French Polynesia / Alexander Mawyer -- Fieldwork as transformative experience: learning to see positive Maori urban identities / Serge A. Marek -- Fieldwork on two wheels in Hanoi, Vietnam, or, How I learned to stop worrying and enjoy the ride / Margaret Barnhill Bodemer -- The cultural power of robots in Japan / Hirofumi Katsuno -- Encountering Maoist propaganda in pastoral Inner Mongolia / Hong Jiang -- When the field is your home: doing advocacy work and academic work in Hawaiʻi / Jonathan Y. Okamura -- Systemic culture shock: meeting Fu Lai Ming on the Tibetan plateau / Naomi C.F. Yamada -- Shoon Pakin, soou tittilap: researching narrative discourse in Micronesia / Emerson Lopez Odango -- Talking with the moai in Easter Island: placing Rapa Nui language / Forrest Wade Young -- Blogging in Papua New Guinea / Steven Edmund Winduo -- Prostitutes, menstrual blood, minor-wives, and feeding the ducks: learning about gender in Thailand / LeeRay M. Costa -- Manning up: on being a Chamorro researcher with a home court (dis)advantage on Guam / James Perez Viernes -- Contested belonging of North Korean refugees in South Korea / Hyeon Ju Lee -- "You Filipino, ya?" / Roberick N. Labrador -- Sorry, wrong number!: locating marriage partners through wrong numbers and text messages in Vanuatu / Ashley Vaughan -- The invisible firewalker: negotiating sentiment and inalienable possessions on a Fijian island / Guido Carlo Pigliasco -- "You can do it, Japan!": social networks and natural disasters / Pamela L. Runestad -- Head candy/gut connection: how reenacting a historic event changes the present in Hawaiʻi / Lynette Hiʻilani Cruz
Bibliographic Level Mode of Issuance: Monograph.
Includes bibliographical references and index.
Specialized.
English.
Online resource; title from home page (viewed on September 26, 2016).
JSTOR
Keywords: Ethnology -- Fieldwork -- Asia; Ethnology -- Fieldwork -- Oceania; Ethnologie -- Recherche sur le terrain -- Asie; Ethnologie -- Recherche sur le terrain -- Océanie.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Anthropology -- General; Ethnology -- Fieldwork; Asia; Oceania; Anthropology; Social & Cultural Anthropology; Social Sciences